pH-controlled lavender oil capsulation with ABA-type block copolymer and usage in paper coating - ÖZCAN, ARİF; ARMAN KANDIRMAZ, EMİNE; BİRTANE, HATİCE (WILEY, 2020)
The aim of this study is to produce a lavender oil capsules with triblock copolymer and to use these capsules for providing scented paper. Thus, polyethylene oxide-polypropylene glycol-polyethylene oxide (PEO-b-PPG-b-PEO) ABA-type block copolymer was synthesized by means of Atom Transfer Radical Polymerization and the chemical structure of PEO-b-PPG-b-PEO was characterized by ATR-FTIR and H-1-NMR. Moreover, block ratio of the PEO-b-PPG-b-PEO was identified with H-1-NMR. Lavender oil was encapsulated in the polymer by micellization of interactions between hydrophilic-lipophilic-hydrophilic polymer and oil. These interactions include lavender oil and lipophilic block interaction and oil-hydrophilic group repulsion. In addition, hydrophilic groups interacted with water to keep the micelles suspended. The critical micelle concentration and size of the micelles were analysed with SEM. Decomposition of capsules was determined by UV spectroscopy with respect to pH change. Paper coating formulations were prepared with fragrant capsules and coated on paper with laboratory-type coating machine. The colour and gloss of obtained papers were determined by spectrophotometer and glossmeter. As a result, PEO-b-PPG-b-PEO polymer can be used to encapsulate lavender oil, and the resulting capsules have functioned without degradation in the paper coating.
Keywords: encapsulation; block copolymer; lavender oil; coating; micelle; TRANSFER RADICAL POLYMERIZATION; MICROENCAPSULATION; MICROCAPSULES; MELAMINE